Progestin-associated shift of meningioma mutational landscape. (30th November 2017) - Peyre, M; Gaillard, S; de Marcellus, C; Giry, M; Bielle, F; Villa, C; Boch, A L; Loiseau, H; Baussart, B; Cazabat, L; Raffin-Sanson, M L; Sanson, M; et al.
Abstract: Background: Meningiomas are the most common primary tumor of the central nervous system. The relationship between meningioma and progestins is frequently mentioned but has not been elucidated. Patients and methods: We identified 40 female patients operated for a meningioma after long-term progestin therapy and performed targeted next generation sequencing to decipher the mutational landscape of hormone-related meningiomas. A published cohort of 530 meningiomas in women was used as a reference population. Results: Compared with the control population of meningiomas in women, progestin-associated meningiomas were more frequently multiple meningiomas [19/40 (48%) versus 25/530 (5%), P < 10 −12 ] and located at the skull base [46/72 (64%) versus 241/481 (50%), P = 0.03]. We found a higher frequency of PIK3CA mutations [14/40 (35%) versus 18/530 (3%), P < 10 −8 ] and TRAF7 mutations [16/40 (40%) versus 140/530 (26%), P < 0.001] and a lower frequency of NF2 -related tumors compared with the control population of meningiomas [3/40 (7.5%) versus 169/530 (32%), P < 0.001]. Conclusion: This shift in mutational landscape indicates the vulnerability of certain meningeal cells and mutations to hormone-induced tumorigenesis. While the relationship between PIK3CA mutation frequency and hormone-related cancers such as breast and endometrial cancer is well-known, this hormonally induced mutational shift is a unique feature in molecular oncology.